PERAN GURU DALAM MENINGKATKAN RENDAHNYA MOTIVASI BELAJAR SISWA KELAS IV A PADA MATA PELAJARAN MATEMATIKA DI MIS AT-TAQWA SAMBAS TAHUN AJARAN 2023-2024 - Wulan Ayuandari; Susilawati, Saripah (ADISAM PUBLISHER, 2024)
This research began with the discovery of the phenomenon of low student learning motivation, especially in mathematics subjects, students experiencing difficulties in mathematics lessons.The aim of this research is to describe and analyze teacher planning, implementation and evaluation in increasing student learning motivation in mathematics subjects at MIS At-Taqwa Sambas for the 2023-2024 academic year.This research uses a qualitative approach with a phenomenological type of research. Data collection techniques in this research used observation, interview and documentation techniques. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Data validity checking techniques use source triangulation, technical triangulation, and member checks.The results of this research show that: (1) Planning the teacher's role in overcoming low student learning motivation is by understanding the classroom situation which is done by observing student interactions then preparing teaching methods and learning strategies that are appropriate to the learning material and then preparing the materials. teaching that will be delivered. (2) The teacher's implementation in increasing students' low learning motivation by conveying interesting learning objectives, then at the core stage the teacher involves students who play an active role in the learning process and at the final or closing stage the teacher always evaluates learning by repeating the learning material that has been explained previously, and (3 evaluations of teachers carrying out their role in overcoming low student learning motivation are checking students' achievements by giving practice assignments to students then, giving questions and quizzes to students which then becomes feedback for improving student learning outcomes.